Cardiovascular Disease Risk Factors Among Middle-Aged and Older Adult Vietnamese American Members of a Northern California Health Plan. (January 2023) - Haysbert, Donna B.; Lo, Joan C.; Ramalingam, Nirmala D.; Gordon, Nancy P.
Objective: There is increasing recognition that cardiovascular disease (CVD) risk factors vary by Asian subgroups. We examined CVD risk factor prevalence among Vietnamese adults in a northern California health plan. Methods: We used electronic health record data to examine smoking, overweight/obesity (body mass index ≥23.0 kg/m 2 ), obesity (body mass index ≥27.5 kg/m 2 ), prediabetes, diabetes, and hypertension among middle-aged (n = 12 757; aged 45-64 years) and older (n = 3418; aged 65-84 years) Vietnamese adults, including 37.8% whose preferred language was Vietnamese. Findings were compared with East Asian adults. Results: Current smoking prevalence was 20.3% for middle-aged men, 7.0% for older men, and <1% for women in both age groups. Obesity prevalence was 12.0% for older men, 17.9% for middle-aged men, and 10% for women in both age groups. Among middle-aged men and women, 20.9% and 17.0% had hypertension and 13.5% and 8.5% had diabetes, respectively. Among older men and women, 64.0% and 60.0% had hypertension and 32.8% and 29.3% had diabetes, respectively. In both age groups, Vietnamese language preference was associated with higher risk of smoking (men only) and of diabetes and hypertension (women only). Compared with East Asian adults, Vietnamese adults had lower obesity prevalence but similar prevalence of diabetes, prediabetes, and hypertension. Vietnamese men were more likely and Vietnamese women less likely than East Asian adults to be current smokers. Conclusions: Study results suggest that more research on health conditions, lifestyle, and social factors among Vietnamese American adults is needed to develop culturally competent interventions to reduce CVD risk in this growing ethnic group.